Synthetic retinoid AM80 inhibits IL‐17 production of gamma delta T cells and ameliorates biliary atresia in mice. (14th September 2020) - Möhn, Nora; Bruni, Elena; Schröder, Arne; Frömmel, Stephanie; Gueler, Faikah; Vieten, Gertrud; Prinz, Immo; Kuebler, Joachim F.; Petersen, Claus; Klemann, Christian
Abstract: Background & Aims: Recent evidence suggests that Interleukin (IL)‐17‐producing gamma delta ( γ δ ) T cells are the dominant pathogenic cellular component in designated autoimmune or inflammatory diseases, including biliary atresia (BA). We have previously demonstrated that retinoids effectively suppress T‐helper cell (Th) 17 differentiation. Methods: Here, we established an in vitro system, enabling investigations of the effect of AM80 on the IL‐17 production of γ δ T cells. Additionally, we tested the therapeutic effect of AM80 in the Rotavirus‐induced mouse model of BA. Co‐incubation of γ δ T cells with IL‐23 and anti‐CD28 mAb proved most effective in inducing an IL‐17 response in vitro. The effect of AM80 on human CCR6+CD26+ V δ 2 cells was assessed by flow cytometry. Results: AM80 efficiently reduced IL‐17 production by murine γ δ T cells and the expression of the master transcription factor Retinoid‐Orphan‐Receptor‐ γ t (ROR γ τ ) in a dose‐dependent manner. The fraction of human CCR6+CD26+ V δ 2 cells was significantly reduced by co‐incubation with AM80. Moreover, AM80 also inhibited IL‐17 production by liver‐infiltrating γ δ T cells isolated from animals suffering from BA. Intraperitoneal treatment with AM80 ameliorated BA‐associated inflammation. However, AM80 treatment was not sufficient to control disease progression in the murine model, despite reduced inflammatory activity in the animals. Conclusions: Retinoids are very efficient in down‐regulating IL‐17 production by γ δ T cells in vitro and, to a lesser extent, in the BA mouse model. However, retinoids do not suffice for the control of disease progression. Thus, our data suggest that IL‐17 is not the only factor contributing to the pathogenesis of BA. Lay summary: Biliary atresia (BA) is a rare disease which affects infants, causing progressive liver failure in most children, and is the most common indication for paediatric liver transplantation. We have previously demonstrated that IL‐17, produced by γ δ T cells, contributes to hepatic inflammation in the murine model of BA and is increased in the livers of infants suffering from the disease. In the study at hand, we demonstrate that treatment with AM80, a synthetic retinoid with superior pharmacological properties, effectively inhibits the IL‐17 production of gamma delta T cells without generating systemic immunosuppression. Although all‐trans retinoic acid (ATRA) has been demonstrated to suppress differentiation of IL‐17‐producing conventional T‐helper cells (Th17) in vitro, the therapeutic application of ATRA in vivo is limited by the compound's potential side effects caused by its instability and lack of receptor specificity. Our study is the first to show that AM80 suppresses the IL‐17 production of γ δ T cells in a very efficient manner and that hepatic inflammation is ameliorated in mice suffering from BA. However, AM80 treatment does not suffice to block the disease progression. We conclude that factors other than IL‐17 drive the progressive inflammation in BA. The addition of retinoids to the treatment regime of children suffering from BA might decrease the disease burden; however, further research is needed to clarify the pathomechanism and possible therapeutic interventions in humans.